Pelestarian Ruang Sakral Permukiman Tradisional Adat Sentani Di Danau Sentani Papua - Deasy Widyastomo (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Historically, the outer space structure of the Sentani traditional defense settlement is an ancestral formation aimed at protecting its citizens from outside intervention and defending themselves from tribal wars. The phenomenon of this ancestral formation is maintained until now as a pattern of traditional Sentani defense settlements. From the previous research has been stated, research on traditional settlement patterns on the meaning of defense and the sacredness of outer spatial planning has never been carried out. No research reveals that the sacred outer space in the traditional Sentani settlement is a phenomenon formed by a sacred defense space to protect indigenous peoples from intervention and tribal wars. The research method used is a qualitative approach using the Intrisic Case Study Approach model with the nature of descriptive research. Data analysis in this study used the method of Discovering Cultural Themes. The locus of this research is the oldest village written in historical references and the Sentani traditional village on Lake Sentani today. The data collection method used observation, in-depth participant interviews, measurable pictures, and photographs. The study results found that the structure of the sacred outer space of the traditional settlements formed by the ancestors is still maintained today as a pattern of traditional Sentani defense settlements. The structural pattern of the sacred space forms a defense space in the traditional Sentani settlement forming a sacred outdoor layout for the Sentani indigenous people with one entrance for visitors or guests to the traditional village, namely a wooden pier for the boat landing. The sacred outer spatial arrangement is indicated by the position of the "Obe Imae" traditional house as the center of activity and customary activities are located at the very front, the two customary zones as the seat of tribal chiefs (traditional devices), the third community zone as the residential space of indigenous peoples, the fourth zone ancestors (traditional graves) and the fifth highest worship zone, namely the church as a place of worship to God.